Alkyl-modified oligonucleotides as intercalating vehicles for doxorubicin uptake via albumin binding - Purdie, Laura; Alexander, Cameron; Spain, Sebastian G.; Magnusson, Johannes P. (American Chemical Society, 2018)
DNA-based drug delivery vehicles have displayed promise for the delivery of intercalating drugs. Here, we demonstrate that oligonucleotides modified with an alkyl chain can bind to human serum albumin, mimicking the natural binding of fatty acids. These alkyl-DNA-albumin complexes display excellent serum stability and are capable of strongly binding doxorubicin. Complexes are internalized by cells in vitro, trafficking to the mitochondria, and are capable of delivering doxorubicin with excellent efficiency resulting in cell death. However, the cellular localization of the delivered doxorubicin, and ultimately the complex efficacy, is dependent on the nature of the linker between the alkyl group and the oligonucleotide.